Do NGO Restrictions Limit Terrorism? Smear Campaigns or Counterterrorism Tools. Issue 1 (11th January 2022) - Koo, Jeong-Woo; Murdie, Amanda
Abstract: Do initiatives to limit nongovernmental organization (NGO) activities work to limit terrorist attacks? Despite regime rhetoric, we argue that NGO restrictions and repression can heighten grievances and limit nonviolent options for citizens to express dissent, broadening support for terrorists and increasing terrorist incidents. Using novel data on NGO restrictions, we fail to find evidence that legal restrictions on NGOs reduce the number of terrorist attacks. Once we account for the unobservable factors that influence both the adoption of these initiatives and the terrorist violence via treatment effects regression models, we find much evidence that NGO restrictions instead exacerbate terrorism. Our findings call into question the counterterrorism and security benefits often used by regime leaders to justify restrictions and all-out repression to NGOs.